Caveats for high reliability in healthcare. Issue 5 (20th August 2018) - Martelli, Peter F.; Rivard, Peter E.; Roberts, Karlene H.
Abstract : Purpose: Given the pace of industry change and the rapid diffusion of high reliability organization (HRO) approaches, lags and divergences have arisen between research and practice in healthcare. The purpose of this paper is to explore several of these theory-practice gaps and propose implications for research and practice. Design/methodology/approach: Classic and cutting-edge HRO literature is applied to analyze two industry trends: delivery system integration, and the confluence of patient-as-consumer and patient-centered care. Findings: Highly reliable integrated delivery systems will likely function very differently from classic HRO organizations. Both practitioners and researchers should address conditions such as how a system is bounded, how reliable the system should be and how interdependencies are handled. Additionally, systems should evaluate the added uncertainty and variability introduced by enhanced agency on the part of patients/families in decision making and in processes of care. Research limitations/implications: Dramatic changes in the sociotechnical environment are influencing the coupling and interactivity of system elements in healthcare. Researchers must address the maintenance of reliability across organizations and the migration of decision-making power toward patients and families. Practical implications: As healthcare systems integrate, managers attempting to apply HRO principles must recognize how these systems present new and different reliability-related challenges and opportunities. Originality/value: This paper provides a starting point for the advancement of research and practice in high-reliability healthcare by providing an in-depth exploration of the implications of two major industry trends.